Presidential Framing in the 21st Century News Media: The Politics of the Affordable Care Act - Hopper, Jennifer Rose (Routledge, 2017)
The Patient Protection and Affordable Care Act came into existence at a time when the president’s ability to lead the public was in question, political polarization had intensified, and the media environment appeared ever more fragmented, fast-moving, and resistant to control. Under such circumstances, how can contemporary American presidents such as Barack Obama build and maintain support for themselves and their policies, particularly as controversies arise? Using case studies of major contests over how key elements of the Affordable Care Act would be framed, and analysis of how those frames fared in influential and popular U.S. news sources, Hopper examines the conditions under which the president can effectively shape public debates today. She argues that despite the difficult political and communications context, the president retains substantial advantages in framing major controversial issues for the media and the public. These presidential framing advantages are conditional, however, and Hopper explores the factors that help make presidential frames more or less likely to gain hold in the news today. More so than in the past, an element of unpredictability in this news environment means that in pursuing favorable messaging, the president and his surrogates may also generate some unintentional consequences in how issues are portrayed to the public. Presidential frames can evolve with unfolding events to take on new meanings and applications, a process facilitated alternately by supporters, opponents, and media actors. Still, media figures and political opponents remain largely reactive to presidential communications, even as some seek to publicize and exploit weaknesses in the administration’s narratives. A close look at these recent cases casts new light on the scholarly debate surrounding the president’s ability to persuasively communicate and challenges conventional wisdom that the 21st century media largely present an unmanageable news environment for the White House. Presidential Framing in the 21st Century News Media engages with current events in American politics, focusing on the Obama Administration and the Affordable Care Act, while also reflecting upon the state of the American presidency, the news media, and the public in ways that have substantial implications for all of these actors, not merely in the present, but into the future, making it a compelling read for scholars of Political Science, Media Studies, Communication Studies, and Public Policy. © 2017 Taylor & Francis.
Keywords: Public opinion; United States. Patient Protection and Affordable Care Act; Health care reform; United States; Medical policy; United States; Medicare; dept.psc; faculty_collection

Reexamining the Nineteenth-Century presidency and partisan press: The Case of President Grant and the Whiskey Ring Scandal - Hopper, Jennifer Rose (Social Science History, 2018)
Studies of the institutional development of the presidency and popular leadership by presidents over time lead us to contrary expectations as to how a nineteenth-century president would react to a major political scandal. Scholarship on newspapers of the late 1800s is also unclear on how a quasipartisan media, with some outlets moving toward independence, would cover a White House scandal. I find that a close analysis of the case of President Ulysses S. Grant and the Whiskey Ring scandal forces us to reconsider what we assume to be firmly modern developments in both presidential studies and media history. Though a supposedly “premodern” president, Grant still mounted a concerted effort to mitigate the damage of the scandal. Further, although the president could get his version of events across in prominent newspapers, Republican newspaper coverage was hardly reliable. Newspapers also connected politicians’ character and psychology to mistakes made in office and made presidential strategies to shape public perception clear to their audiences—emphases on political gamesmanship considered hallmarks of the modern media environment.
Keywords: dept.psc; peer-reviewed